Corticosteroid injections for tennis elbow – A hard habit to break. (September 2015) - Inklebarger, James; Clarke, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives In the UK, serial cortisone injections (CSI) to manage lateral epicondylitis (LE) is a routine practice. This remains so despite LE histopathological studies reporting chronic common extensor origin degenerative tendonopathy rather than inflammatory change. Several RCT studies have also demonstrated a lack of clinical efficacy for using CSI for LE, with more favourable outcomes achieved through autologous blood and platelet-rich plasma injections. Methods This case study follows a presentation in which corticosteroid injection (CSI) for LE was followed by recurrence of pain after initial relief. Results/Discussion An assessment of other options discussed in the literature led to a resolution of symptoms with a combination of enforced abatement of flaring activities and physiotherapist supervised graded forearm eccentric loading program, rather than repetition of the CSI.